2012
DOI: 10.1016/j.ijid.2012.05.192
|View full text |Cite
|
Sign up to set email alerts
|

The effect of andrographolide on Human papillomavirus type 16 (HPV16) positive cervical cancer cells (SiHa)

Abstract: Background: Infection with a high-risk human papillomavirus (HR-HPV), especially, HPV16 is the most important risk factor for cervical cancer. Oncoproteins (E6 and E7) of HR-HPV play an important role in cervical cancer development involved by several mechanisms including degradation of tumor suppressor protein p53 and anti-apoptosis. Andrographolide is a diterpenoid lactone isolated from a traditional herbal medicine,Andrographis paniculata. It has been reported to induce apoptosis in different cancer cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A recent study also reported a similar number of unique secondary metabolites [169]. Among these compounds, about 80 compounds showed different types of pharmacological activities, including antibacterial [109,139,[170][171][172][173][174][175], anti-biofilm [88,176], antiviral (i.e., chikungunya virus [91], Anti-HIV [177][178][179], anti-influenza [99,180], Herpes simplex virus 1 [83,99,181], dengue virus serotype 1 [92][93][94]182], anti-Epstein Barr virus [97], pestivirus and flavivirus [90], human papillomavirus type 16 [96]), anti-fungal [109,183], antiparasitic (i.e., antimalarial [95,184,185], anti-Leishmaniasis [98]), antiproliferative [85][86][87]120,122,124,127,128,177,186], cytotoxicity [84][85][86]…”
Section: Antimicrobial Secondary Metabolites Of a Paniculatamentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study also reported a similar number of unique secondary metabolites [169]. Among these compounds, about 80 compounds showed different types of pharmacological activities, including antibacterial [109,139,[170][171][172][173][174][175], anti-biofilm [88,176], antiviral (i.e., chikungunya virus [91], Anti-HIV [177][178][179], anti-influenza [99,180], Herpes simplex virus 1 [83,99,181], dengue virus serotype 1 [92][93][94]182], anti-Epstein Barr virus [97], pestivirus and flavivirus [90], human papillomavirus type 16 [96]), anti-fungal [109,183], antiparasitic (i.e., antimalarial [95,184,185], anti-Leishmaniasis [98]), antiproliferative [85][86][87]120,122,124,127,128,177,186], cytotoxicity [84][85][86]…”
Section: Antimicrobial Secondary Metabolites Of a Paniculatamentioning
confidence: 99%
“…[39,176,192,193]. [139,[170][171][172][173], anti-biofilm [88,139], anti-CHIKV [91], Anti-HIV [177][178][179], anti-influenza [99,180], anti-HSV-1 [83,99,181], anti-DVS-1 [92][93][94]182], anti-EBV [97], anti-HPV-16 [96], anti-HBV [186], anti-HCV [194], antimalarial [95,184,185], anti-Leishmaniasis [98] [190,191] AeP…”
Section: Antimicrobial Secondary Metabolites Of a Paniculatamentioning
confidence: 99%
“…Researchers investigated significant antiviral activity of AP besides other pharmacological activities in last two decades. Although they reported antiviral activity against limited viruses, such as dengue virus serotype 1 (DENV-1) [ 201 ], human papilloma virus type 16 (HPV16) [ 202 ], herpes simplex virus type 1 (HSV-1) [ 203 ], influenza A virus [ 102 ], and HIV [ 53 , 55 , 80 , 204 ], their findings were very encouraging and noteworthy considering the life threatening role of these viruses in human community. The hot aqueous aerial parts extract of AP was reported for its significant antiviral activity to reduce the percentage of HIV antigen-positive H9 cells [ 55 ].…”
Section: Potential Pharmacologymentioning
confidence: 99%
“…Recently, Tang et al [ 201 ] reported that the methanol extract of AP possesses significant inhibition activity against DENV-1 in vitro assay. Another study has revealed that andrographolide suppressed HPV16 transcription activity, leading to the reduction of E6 oncoprotein and restored p53 [ 202 ].…”
Section: Potential Pharmacologymentioning
confidence: 99%
“…f.) Nees (family Acanthaceae) contains diverse compounds such as labdane diterpenoid lactones, flavonoids, and miscellaneous compounds and is widely used as a traditional medicine in Asian countries [5,7]. Anti-viral activity of andrographolide has been shown for a number of viruses including herpes simplex virus [8], dengue virus (DENV) [9], chikungunya virus (CHIKV) [10], human papillomavirus (HPV) [11], hepatitis B virus (HBV) [12], and influenza A [13].…”
Section: Introductionmentioning
confidence: 99%